Psychological Distress and Its Association With Quality of Life in Organ Transplant Recipients During COVID-19 Pandemic - Cai, Zhongxiang; Cai, Xin; Song, Yujuan; Wang, Dianzhen; Zhang, Yanbing; Ma, Simeng; Tang, Shiming; Bai, Hanping; Tan, Huawei; Li, Ruiting; Yao, Lihua; Liu, Zhongchun; et al. (Frontiers in Psychiatry, 2021)
Objectives: The coronavirus disease 2019 (COVID-19) pandemic may have an impact on the psychological distress of organ transplant recipients. We aimed to assess the status of psychological distress and its association with quality of life (QoL) in organ transplant recipients during the COVID-19 pandemic. Materials and methods:A cross-sectional survey was carried out with 305 organ transplant recipients during March 30 and April 2, 2020, in Wuhan. Psychological distress comprised depression, anxiety, insomnia, and post-traumatic stress disorder (PTSD), which were assessed using the Patient Health Questionnaire-9, the seven-item Generalized Anxiety Disorder questionnaire, the Insomnia Severity Index, and Impact of Event Scale-Revised. QoL was assessed using the Chinese version of the Short Form 36-Item Health Survey. Results: The prevalence of depression, anxiety, insomnia, and PTSD in organ transplant recipients was 13.4%, 6.9%, 11.8%, and 30.5%, respectively. Organ transplant recipients with depression had significantly lower scores in all eight dimensions of QoL compared with participants without depression (all p<0.05). Lower scores on the QoL dimensions of role physical, bodily pain, general health, vitality, role emotional, and mental health were found in organ transplant recipients with anxiety, insomnia, or PTSD compared with their counterparts without the respective disorder (all p<0.05). Limitation: The cross-sectional study design limited us to make causal conclusion and the influence of potential confounders cannot be ruled out. Conclusions: Psychological distress was prevalent in organ transplant recipients during the COVID-19 pandemic, and those with depression, anxiety, insomnia, and PTSD had poorer QoL. Therefore, timely psychological counselling, COVID-19 related health education, and essential community medical services should be provided to organ transplant recipients to relieve their psychological distress, and to improve their QoL.